Active flutter control of delaminated composite plate using active fiber composite patches. (March 2022) - Swain, Prasant Kumar; Tiwari, Pratik; Maiti, Dipak Kumar; Singh, Bhrigu Nath; Maity, Damodar
Abstract: The effect of delamination on flutter characteristics of delaminated plate and control of flutter velocity is presented in this paper. The structural model of the smart delaminated plate is constructed using a 3D degenerated element, where the shear deformation and rotary inertia are considered based on the Reissner–Mindlin assumptions. Using the modal output of the structural model through a direct matrix abstraction program (DMAP), aerodynamic forces are generated from MSC.Nastran. Further flutter analysis is carried out using the p k -method in the MATLAB environment. This MSC.Nastran coupled FE model is thoroughly validated with various examples of dynamic and aeroelastic analysis. The effect of delamination location and interface on flutter characteristics of laminated plate with various boundary conditions are investigated first, and an attempt is made to enhance flutter velocity of the delaminated plate through active control technique. Highlights: A coupled model of FE coding and MSC.Nastran is constructed in MATLAB. The model is developed to perform flutter analysis of smart delaminated plate. Both embedded and through-width delamination is considered for the investigation. The effect of location, and interface of delamination is studied. The investigation is carried out for C-F-C-F and C-F-F-F boundary condition. The AFC patches with interdigitated electrodes are used as sensor and actuator. Active control technique is found to be effective for control of flutter. The regain of flutter velocity lost due to 16.66% delamination is attempted.